Productivity clustering and growth in Central and Eastern Europe - Mihai Nitoi; Maria Miruna Pochea (Baltic Journal of Economics, 2016)
This article uses a non-linear time-varying model to test productivity convergence in 10 emerging countries within Central and Eastern Europe. The results show that the convergence algorithm has rejected the null hypothesis of convergence for all countries in most of the sectors. Also, we found evidence that the productivity clusters for total economy and other sectors are very different in terms of number and countries. Additionally, even if the productivity gaps in the region have been reduced, we still notice significant disparities between countries. The clustering algorithm shows countries which have a high productivity growth in some sectors and a low productivity growth in others. This reveals the prevalence of idiosyncratic factors in productivity determinants. Baltic countries are catching up, while other countries such as Bulgaria are underperformers.
Keywords: O47; O52; J24; C32; C33; 330; Labour productivity; panel convergence methodology; CEE countries; sectoral trends